Dermoscopy and 30% potassium hydroxide direct examination as diagnostic tools for distal lateral subungual onychomycosis - Gaol, Evangelina Lumban; Miranda, Eliza; Sirait, Sondang Pandjaitan (UI Scholars Hub, 2024)
Background: Culture and histopathological examination are gold standards for diagnosing onychomycosis. However, these examinations are subject to several limitations. Dermoscopy has the potential to become a promising diagnostic tool for onychomycosis. Direct examination of potassium hydroxide (KOH) also has advantages similar to dermoscopy. Knowing the accuracy of both examinations can help clinical decision-making. Our objectives are to assess the diagnostic value of dermoscopy, KOH examination, and their combination for distal lateral subungual onychomycosis compared to culture or histopathology. Methods: This was a cross-sectional diagnostic study of nails with suspected distal lateral subungual onychomycosis. Sixty nails were included in this study. Results: The sensitivity and specificity of the KOH examination were 89.6% and 66.7%, respectively. On dermoscopy, the sensitivity of jagged-edge-with-spikes, longitudinal striation, and discoloration were 89.6%, 93.8%, and 97.9%, respectively. Only the aurora borealis dermoscopic feature provided good specificity (91.7%). The positive predictive values of these four dermoscopic features were 75.0%–79.7%. Combination with KOH examination increased the positive predictive value of dermoscopy (90.9%–92.7%). Conclusion: Since they were superior in terms of sensitivity, dermoscopy and KOH examinations are good screening tools to determine which suspected onychomycosis cases need further examination. Additionally, an increased positive predictive value was observed when the two examinations were combined. Hence, these procedures can help establish a diagnosis in settings where mycologic examinations are unavailable.